ANALISIS PRAKTIK PEMBELAJARAN IPS KELAS PGSD - Rizki Ananda; Sri Wartina; Ranti Marsela; Astrid Aprillia; Era Aryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Social Studies (IPS) instruction in elementary schools plays a vital role in shaping students' social attitudes, knowledge, and skills, equipping them for life in society. The quality of Social Studies instruction relies heavily on the teacher's competence in designing and implementing lessons suited to the characteristics of elementary school students; therefore, the instructional practices employed by Primary School Teacher Education (PGSD) students warrant in-depth examination. This article aims to analyze Social Studies instructional practices within the PGSD context covering the aspects of planning, implementation, and evaluationand to identify the strengths and weaknesses inherent in these practices. The study employs a library research method, involving the collection, reading, and analysis of relevant sources such as books, scholarly journals, and prior research findings. Data analysis was conducted using a descriptive-qualitative approach to describe and synthesize findings from the reviewed literature. The results indicate that Social Studies instructional practices in PGSD settings demonstrate positive efforts to link course material to students' real-life experiences, although challenges remain regarding time constraints, the variety of instructional media, and disparities in student participation. The study recommends a more consistent application of contextual and cooperative learning models to enhance the effectiveness of Social Studies instruction. These findings are intended to serve as a basis for reflection for prospective teachers as they develop more meaningful Social Studies instructional practices. Keywords: Instructional Practices, Social Studies (IPS), Primary School Teacher Education (PGSD).